Dental students perception of orthodontic treatment - Baswaraj; K Jayasudha; K M Kumarswamy; M N Padmini; B Chandralekha; D P Shruthi (Wolters Kluwer Medknow Publications, 2015)
Introduction: The relationship between physical appearance and perception of an esthetic deviation, and the impact of such deviation on self-esteem and body image are important issues in determining the benefits of orthodontic treatment. Aim: To assess dental students' perception of orthodontic treatment. Materials and Methods: A total of 230 undergraduate dental students of Government Dental College and Research Institute, Bangalore, Karnataka formed the study group. Each classroom of the participants was visited, and self-administered questionnaire was given. An analysis of variance was done between the groups to test for statistical difference. Categorical variables were evaluated using a Chi-square test with the level of significance of P < 0.001. Results: About 75% of the students were aware of their dental esthetics. About 75% of females were satisfied with the attractiveness of their teeth when compared to 69% in males. House surgeons had more positive attitude compared to the 1 st year students. Conclusion: The dental students had good knowledge about the orthodontic treatment and had a positive attitude toward it. Females had very good knowledge, satisfaction and positive attitude compared to the males regarding dental esthetics and treatment. House surgeons were much more aware, very much satisfied and had a more positive attitude than 1 st year students.